2013
DOI: 10.1088/0953-8984/25/24/246004
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and magnetic structures of the Co-bearing dugganites Pb3TeCo3A2O14(A = V, P)

Abstract: Exhibiting rich magnetic behaviour and potentially multiferroic properties, the dugganites, a Te(6+) containing subgroup of the langasite series, are an attractive family of compounds for future study. It was recently shown that Pb-bearing members of the dugganite series undergo distortions away from the P321 symmetry that is characteristic of the langasites. Here, we detail the consequences these distortions have on the magnetism exhibited by Pb3TeCo3V2O14 and Pb3TeCo3P2O14, solving the magnetic structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Together with ferromagnetic J c and J 2 they relieve frustration and make Co ions neighboring in the c direction to be antiferromagnetically ordered, which agrees with experimental findings. 5,6 We repeated calculation of the exchange constants with slightly smaller U eff and found that with decrease of U eff on 0.5 eV both J d1 + J d2 and J 2 increase in absolute values as expected for superexchange (J d1 + J d2 = 5.3 K, J 2 = -2.0 K), while J 1 and J c practically do not change (J 1 = 0.1 K, J c = 2.6 K).…”
Section: First Principles Calculationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Together with ferromagnetic J c and J 2 they relieve frustration and make Co ions neighboring in the c direction to be antiferromagnetically ordered, which agrees with experimental findings. 5,6 We repeated calculation of the exchange constants with slightly smaller U eff and found that with decrease of U eff on 0.5 eV both J d1 + J d2 and J 2 increase in absolute values as expected for superexchange (J d1 + J d2 = 5.3 K, J 2 = -2.0 K), while J 1 and J c practically do not change (J 1 = 0.1 K, J c = 2.6 K).…”
Section: First Principles Calculationsmentioning
confidence: 99%
“…P121) and multiplicated cell parameters. [4][5][6] The presence of magnetic Co 2+ and Mn 2+ ions in the structure add new, magnetic dimension to langasite's. Magnetic properties in these compounds are related to such substitutions since another transition metal in the structure, vanadium, is pentavalent and do not carry magnetic moment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a Te 6 þ -containing subgroup of the langasites, called the dugganites after the natural mineral Pb 3 TeZn 3 As 2 O 14 [6], has been receiving interest [24][25][26][27][28][29][30]. Te 6 þ allows one to substitute divalent 3d metal ions into the trimer site due to charge balancing and preferential symmetry constraints.…”
Section: Introductionmentioning
confidence: 99%